Pancasila as an Enforcer of Justice and Equality - Fandiatira Junarizki; Farhan Yoga Hamdani; Pandu Aji Prasojo; Riska Andi Fitriono (CV. Rayyan Dwi Bharata, 2022)
Pancasila is the spirit of the people (soul of the nation) which is the ideology of the nation and state. Indonesia needs police who have the soul of Pancasila to build their own integrity and justice in society. The purpose of writing this article is to explain to law enforcement agencies the nature of Pancasila in upholding its own integrity and justice. This writing method is normative writing through an analytical approach. The result of writing this article is that Pancasila has valuable elements that can be used to build integrity for Polri members and has positive energy to realize social justice. The role of Pancasila in enhancing the integrity of law enforcement is to encourage police officers to internalize, investigate, seek and find values in the soul of the community to realize justice which is not only legal, but also social justice. namely justice that respects equality between humans and other humans in society.